1995
DOI: 10.1080/03610929508831632
|View full text |Cite
|
Sign up to set email alerts
|

Critical values and powers for tests of uniformity of directions under multivariate normality

Abstract: The Rayleigh, Ajne, Gin4 and two new tests of uniformity of directions are investigated as tests for multivariate normality when the population mean vector and covariance matrix are assumed to be unknown. The new tests include one which is designed especially to detect for bimodal alternatives and one which is designed to perform well under a wide variety of alternatives. Simulated percentile points are obtained under the assumption that the variates constitute a random sample from a multivariate normal distri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2002
2002
2004
2004

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Uniformity of the angles indicates normality of the multivariate data. Dunn (1995) suggested that Koziol's 'radii and angles' test could be improved by replacing the Rayleigh test statistic for uniformity with a more powerful substitute. Tsai & Koziol (1988) presented a procedure that utilized the correlation coefficient of the chi-square plot.…”
Section: Graphical and Correlational Approachesmentioning
confidence: 99%
“…Uniformity of the angles indicates normality of the multivariate data. Dunn (1995) suggested that Koziol's 'radii and angles' test could be improved by replacing the Rayleigh test statistic for uniformity with a more powerful substitute. Tsai & Koziol (1988) presented a procedure that utilized the correlation coefficient of the chi-square plot.…”
Section: Graphical and Correlational Approachesmentioning
confidence: 99%